Technological Frames and Learning Experiences: Students’ Interpretations of Rule-Based Chatbots in Higher Education - Alanko-Turunen, Merja; Kupiainen, Olli-Jaakko; Raaska, Mari (38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings, 2025)
This study examines how students construct technological frames of rule-based chatbots and how these frames relate to their learning experiences, particularly information processing and reflection. This research is grounded in the social construction of technology and technological frames theory. Semi-structured interviews were conducted with 45 undergraduate students at a University of Applied Sciences. Through thematic analysis, three distinct technological frames were identified: collaborative, completion-driven, and unhelpful. Each frame was found to shape how chatbot technology was engaged with and integrated into students’ learning processes. This study extends technological framing theory to the educational field, linking technological frames to students' learning experiences. We also provide an empirically grounded framework that helps understand student learning experiences within chatbot-supported learning environments. This research contributes to an understanding of how interpretations of technology construct educational experiences and emphasizes the critical relationship between pedagogy and technology.